2006
DOI: 10.1002/jcp.20664
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐I increases bone sialoprotein (BSP) expression through fibroblast growth factor‐2 response element and homeodomain protein‐binding site in the proximal promoter of the BSP gene

Abstract: Insulin-like growth factor-I (IGF-I) promotes bone formation by stimulating proliferation and differentiation of osteoblasts. Bone sialoprotein (BSP), is thought to function in the initial mineralization of bone, is selectively expressed by differentiated osteoblast. To determine the molecular mechanism of IGF-I regulation of osteogenesis, we analyzed the effects of IGF-I on the expression of BSP in osteoblast-like Saos2 and in rat stromal bone marrow (RBMC-D8) cells. IGF-I (50 ng/ml) increased BSP mRNA levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 62 publications
0
60
0
1
Order By: Relevance
“…Among the genes differentially expressed in Dlx3 OCN-cKO metaphysis, DLX5 has been shown to regulate and bind to the promoter regions of Runx2, 10 Hox family members, 28 Sp7, 38 Alpl 39 and Ibsp. 40,41 These data together with our ChIP results demonstrating DLX3 binding to some of these genes lead us to speculate that DLX3 and DLX5 may have a coordinated role in the transcription of bone-related genes via molecular switches at their promoter regions.…”
Section: Dlx5/dlx6mentioning
confidence: 59%
“…Among the genes differentially expressed in Dlx3 OCN-cKO metaphysis, DLX5 has been shown to regulate and bind to the promoter regions of Runx2, 10 Hox family members, 28 Sp7, 38 Alpl 39 and Ibsp. 40,41 These data together with our ChIP results demonstrating DLX3 binding to some of these genes lead us to speculate that DLX3 and DLX5 may have a coordinated role in the transcription of bone-related genes via molecular switches at their promoter regions.…”
Section: Dlx5/dlx6mentioning
confidence: 59%
“…Activation of PKA may induce CREB1 phosphorylation, and phospho-CREB1 can bind firmly to CRE, thereby inducing gene transcription (51). HA, U0126 and LY294002 have been shown to inhibit the increased binding activities of transcription factors to the FRE and HOX elements in the rat BSP gene promoter (35). In our previous study, we showed that FGF2 stimulated BSP gene transcription via the tyrosine kinase and ERK1/2 pathways (33), PTH activated cAMP and phospholipase C through the PKA and tyrosine kinase pathways (31), and PGE2 increased BSP transcription via PKA, tyrosine kinase and ERK1/2, which target nuclear proteins binding to CRE and FRE in the rat BSP gene promoter (34).…”
Section: Discussionmentioning
confidence: 99%
“…In the human BSP gene promoter, an inverted TATA box (nts -28~-23) (27) and an inverted CCAAT box (nts-54~-50) maintain basal transcription (29,30), and two cAMP response elements (CRE1; -79~-72, CRE2; -674~-667) are also present (31,32). Additionally, a fibroblast growth factor 2 (FGF2) response element (FRE; nts -96~-89) (33,34), three activating protein 1 (AP1) response elements (AP1(1); -148~-142, AP1(2); -483~-477 and AP1(3); -797~-791) (31,32), and a homeobox binding site (HOX; -200~-191) (35,36) have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, IGFs stimulate in vitro and in vivo osteoblast proliferation and differentiation through specific membrane receptors [18][19][20][21] .…”
Section: Introductionmentioning
confidence: 99%